Gender responsiveness in the counseling sessions of the Empowerment and Welfare Organization (PKK) in an attempt to increase family resilience in Cilacap Regency - Dyah Retna Puspita; Rin Rostikawati; Pawrtha Dharma (Faculty of Social and Political Science, Universitas Airlangga, 2018)
This research, which was conducted in Cilacap Regency, aimed to study the level of gender responsivity in the counseling sessions ran by the Empowerment and Welfare Organization (hereafter, PKK) at the sub-district and village/urban village levels for society members focused on where the divorce rate is high, particularly those where the divorces were fled by the wives. The research approach was a mixed methodology, implementing both quantitative and qualitative methods at the same time. The samples were taken from three sub-districts which had recorded the highest divorce rates recently. The research population was all of the committee members of PKK in the three sub-districts and villages, which consisted of 180 people. The data were obtained from a questionnaire and focus group discussion, analyzed using descriptive statistics, and refined by gender perspectives. The findings showed that the committee members’ understanding of divorce, family resilience, and gender issues in Cilacap was relatively low. This then aﬀected gender responsivity in their counseling sessions. Low gender responsiveness was signaled by gender stereotyping in relation to targeting the counseling participants (only for the females/wives in each district, without involving the male group at all). Moreover, the counseling materials have not alluded to the rising divorce issue in these areas. As a result, this issue has not received enough attention, particularly among males/husbands. This is even though there are various forums in the neighborhood (RT) and hamlet (RW) levels (in which the major participants are males/husbands) which can accommodate them, raising awareness of these issues and trying to find solutions. Such conditions cannot be separated from the centralized organizational structure of PKK, in which these activities are decided by policies at the regency, province, and central governmental levels. There are no specific policies at the central government level for the prevention and treatment of divorce issues; hence, these issues have not received an adequate amount of attention in the areas with a high divorce rate. PKK at the regency level is more focused on the socialization of parenting patterns, which is also emphasized at the provincial level. As a result, PKK at the regency level has no accurate data on the rising divorce rate within the stated areas.